The Ambiguity of Resi Gudang (Warehouse Receipt) Guarantee Institution Legal Standing - Safira Oktavia Putri (NORMA, 2021)
Farmers usually use warehouse receipts to obtain debt with commodity objects stored in the warehouse as a debt security. Warehouse receipts as valuable objects, of course, have the potential to be tied up in a debt bond that serves as a security for these debts. However, for an item of guarantee, the legal aspects are quite diverse. For objects to be used as collateral in a credit agreement, they must meet certain conditions, namely, economic value and transferability. Therefore, it is necessary to conduct a study of warehouse receipts to be used as collateral objects, given the characteristics of warehouse receipts as valuable objects and the property rights attached to the warehouse receipts. This research is normative research with a statutory approach. The result of this research is that warehouse receipts can be used as collateral objects but with some adjustments. And based on the existing regulations, it is understood that the warehouse receipt arrangement does not create a warehouse receipt guarantee institution.Keywords: Resi Gudang, Debt, Collateral